Postcardiotomy Venoarterial Extracorporeal Membrane Oxygenation in Patients Aged 70 Years or Older - Biancari, Fausto; Saeed, Diyar; Fiore, Antonio; Dalén, Magnus; Ruggieri, Vito G; Jónsson, Kristján; Gatti, Giuseppe; Zipfel, Svante; Dell'Aquila, Angelo M; Chocron, Sidney; Bounader, Karl; Amr, Gilles; et al. (The Annals of thoracic surgery, 2019)
BACKGROUND: There is uncertainty whether venoarterial extracorporeal membrane oxygenation (VA-ECMO) should be used in older patients with cardiopulmonary failure after cardiac surgery. METHODS: This was a retrospective multicenter study of 781 patients who required postcardiotomy VA-ECMO for cardiopulmonary failure after adult cardiac surgery from 2010 to 2018 at 19 cardiac surgery centers. A parallel systematic review with meta-analysis of the literature was performed. RESULTS: The hospital mortality in the overall Postcardiotomy Venoarterial Extracorporeal Membrane Oxygenation (PC-ECMO) series was 64.4%. A total of 255 patients were 70 years old or older (32.7%), and their hospital mortality was significantly higher than in younger patients (76.1% vs 58.7%; adjusted odds ratio, 2.199; 95% confidence interval [CI], 1.536 to 3.149). Arterial lactate level greater than 6 mmol/L before starting VA-ECMO was the only predictor of hospital mortality among patients 70 years old or older in univariate analysis (82.6% vs 70.4%; P = .029). Meta-analysis of current and previous studies showed that early mortality after postcardiotomy VA-ECMO was significantly higher in patients aged 70 years or older compared with younger patients (odds ratio, 2.09; 95% CI, 1.59 to 2.75; 5 studies including 1547 patients; I2, 5.9%). The pooled early mortality rate among patients aged 70 years or older was 78.8% (95% CI, 74.1 to 83.5; 6 studies including 617 patients; I2, 41.8%). Two studies reported 1-year mortality (including hospital mortality) of 79.9% and 75.6%, respectively, in patients 70 years old or older. CONCLUSIONS: Advanced age should not be considered a contraindication for postcardiotomy VA-ECMO. However, in view of the high risk of early mortality, meaningful scrutiny is needed before using VA-ECMO after cardiac surgery in older patients.
Keywords: kardiochirurgické výkony; respirační insuficience; Humans; lidé středního věku; mimotělní membránová oxygenace; výběr pacientů; Patient Selection; Female; Aged; srdeční zástava; věkové faktory; senioři; lidé; mortalita v nemocnicích; Extracorporeal Membrane Oxygenation; Cardiac Surgical Procedures; Postoperative Complications; pooperační komplikace; ženské pohlaví; Male; Middle Aged; Retrospective Studies; retrospektivní studie; Respiratory Insufficiency; Age Factors; Hospital Mortality; Heart Arrest; mužské pohlaví